Anxiety sensitivity and sleep disturbance: Investigating associations among patients with co-occurring anxiety and substance use disorders. (January 2018) - Dixon, Laura J.; Lee, Aaron A.; Gratz, Kim L.; Tull, Matthew T.
Highlights: Anxiety sensitivity (AS) was examined in relation to insomnia and somnolence. The sample included 99 residential SUD patients with anxiety disorders. 53.5% of the sample reported clinical levels of insomnia or somnolence. AS cognitive, but not physical, concerns were associated with sleep disturbance. Results support AS interventions for dual diagnosis patients with sleep problems. Abstract: Sleep disturbance is a common problem among individuals with anxiety and substance use disorders (SUD). Anxiety sensitivity (AS) is elevated in patients with anxiety disorders and SUD and has been linked to sleep-related problems, including insomnia and somnolence (i.e., daytime sleepiness). We examined the unique roles of AS cognitive, physical, and social concerns in sleep disturbance among a sample of 99 residential SUD patients with anxiety disorders. Clinical levels of insomnia or somnolence were evidenced by 53.5% of the sample. Consistent with predictions, AS physical concerns was significantly associated with insomnia, and AS cognitive concerns was significantly related to insomnia and somnolence. Hierarchical linear regression models were conducted to test the association of AS cognitive and physical concerns with insomnia and somnolence symptoms while controlling for relevant factors. AS cognitive concerns accounted for unique variance, above and beyond withdrawal symptoms, anxiety, and depressive symptoms, in the model examining insomnia symptoms ( B  = 0.30, SE  = 0.13, p  = 0.023). Results suggest that AS cognitive concerns may represent an important transdiagnostic mechanism underlying sleep disturbance among individuals with dual diagnosis.